2020
DOI: 10.3389/fnins.2020.00202
|View full text |Cite
|
Sign up to set email alerts
|

Early Dendritic Morphogenesis of Adult-Born Dentate Granule Cells Is Regulated by FHL2

Abstract: Dentate granule cells (DGCs), the progeny of neural stem cells (NSCs) in the subgranular zone of the dentate gyrus (DG), must develop and functionally integrate with the mature cohort of neurons in order to maintain critical hippocampal functions throughout adulthood. Dysregulation in the continuum of DGC development can result in aberrant morphology and disrupted functional maturation, impairing neuroplasticity of the network. Yet, the molecular underpinnings of the signaling involved in adult-born DGC matura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…As numerous studies indicate, epilepsy’s pathology is intricate and encompasses a wide-range of mechanisms, several of which may serve as therapeutic targets for stem-cell based remedies. Indeed, irregular neuronal pathways, potentially engendered by the dysregulated construction of the neuronal network, has been associated with epilepsy ( Homan et al, 2018 ; Schuster et al, 2019 ; Ahamad et al, 2020 ). Impaired dentate granule cell (DGC) development from NSCs may spur warped hippocampal activity, neuroplasticity, and formation of mature neurons, which would lead to hippocampal-related disorders like mesial temporal lobe epilepsy (MTLE) ( Ahamad et al, 2020 ).…”
Section: Recent Preclinical and Clinical Evidence Supporting The Safementioning
confidence: 99%
See 3 more Smart Citations
“…As numerous studies indicate, epilepsy’s pathology is intricate and encompasses a wide-range of mechanisms, several of which may serve as therapeutic targets for stem-cell based remedies. Indeed, irregular neuronal pathways, potentially engendered by the dysregulated construction of the neuronal network, has been associated with epilepsy ( Homan et al, 2018 ; Schuster et al, 2019 ; Ahamad et al, 2020 ). Impaired dentate granule cell (DGC) development from NSCs may spur warped hippocampal activity, neuroplasticity, and formation of mature neurons, which would lead to hippocampal-related disorders like mesial temporal lobe epilepsy (MTLE) ( Ahamad et al, 2020 ).…”
Section: Recent Preclinical and Clinical Evidence Supporting The Safementioning
confidence: 99%
“…Indeed, irregular neuronal pathways, potentially engendered by the dysregulated construction of the neuronal network, has been associated with epilepsy ( Homan et al, 2018 ; Schuster et al, 2019 ; Ahamad et al, 2020 ). Impaired dentate granule cell (DGC) development from NSCs may spur warped hippocampal activity, neuroplasticity, and formation of mature neurons, which would lead to hippocampal-related disorders like mesial temporal lobe epilepsy (MTLE) ( Ahamad et al, 2020 ). It has been indicated that FHL2 protein is involved with dentate gyrus metabolism and neurogenesis ( Ahamad et al, 2020 ).…”
Section: Recent Preclinical and Clinical Evidence Supporting The Safementioning
confidence: 99%
See 2 more Smart Citations